Mechanical performance of recycled aggregate self-consolidating concrete column - Yu, Feng; Feng, Chaochao; Wang, Shilong; Huang, Wei; Fang, Yuan; Bu, Shuangshuang (Journal of Civil Engineering and Management, 2021)
The utilization of recycled concrete aggregate (RCA) can reduce the environmental impact and decreases the cost of concrete. In this study, a comprehensive assessment of self-consolidating concrete (SCC) using RCA as partial or total replacement of coarse aggregate was conducted. Recycled concrete aggregate self-consolidating concrete (RCA-SCC) mixtures with varied water-to-cement (W/C) ratios (0.28–0.46), sand-to-aggregate (S/A) ratios (48–52%), fly ash (FA) contents (20–40%), RCA replacement ratios (0–100%), and water reducer contents (0–1.5%) were designed and tested.  5 groups of the RCA-SCC columns with different W/C and replacement ratios of RCA were also investigated. The slump flow, the J-ring flow and the cubic compressive strength, and the compressive behaviors of the RCA-SCC columns were studied. Results indicated that W/C ratio was the dominant parameter in RCA-SCC mixture, and the failure modes of the RCA-SCC columns were similar to those of the conventional concrete columns. Based on the experimental results, the mechanical performance of RCA-SCC columns was evaluated quantitatively, and a stress–strain relation model for predicting the axial compressive behavior of RCA-SCC column was proposed. This study will provide a reference for the engineering application of the environment-friendly SCC using RCA that are derived from tested or returned concretes with better performance.